Household Credit, Global Financial Cycle, and Macroprudential Policies: Credit Register Evidence from an Emerging Country - Mircea Epure; Irina Mihai; Camelia Minoiu; José-Luis Peydró (Universitat Pompeu Fabra (upf), Department of Economics and Business, 2018)
We analyze the effects of macroprudential policies on local bank credit cycles and their interactions with international financial conditions. To this end, we exploit the comprehensive credit register containing all bank loans to individuals in Romania, a small open economy subject to external shocks. Our sample period from 2004 until 2012 covers a full boom-bust credit cycle during which a wide range of macroprudential measures were deployed. Our results show that tighter macroprudential conditions are associated with a significant decline in household credit, with substantially stronger effects for FX loans than for local currency loans. The effects on FX loans are higher for: (i) ex-ante riskier borrowers proxied by higher debt-service-to-income ratios and (ii) banks with greater reliance on foreign funding. Furthermore, tighter macroprudential policy has stronger dampening effects on FX lending when global risk appetite is high and foreign monetary policy is expansionary. Quantitative effects are in general larger for borrower rather than lender macroprudential policies. Overall, the results suggest that macroprudential policies are effective in mitigating bank risk-taking in household lending over the local bank credit and global financial cycles and have important implications for theory and policy.
Keywords: G01; G21; G28; 330; macroprudential policies; global financial cycle; boom-bust credit cycle; household credit; bank loans